Chemotherapeutic copolymers prepared via the RAFT polymerization of prodrug monomers. Issue 27 (17th June 2016) - Son, H. N.; Srinivasan, S.; Yhee, J. Y.; Das, D.; Daugherty, B. K.; Berguig, G. Y.; Oehle, V. G.; Kim, S. H.; Kim, K.; Kwon, I. C.; Stayton, P. S.; Convertine, A. J.
Abstract : Reversible addition–fragmentation chain transfer (RAFT) polymerization was employed to prepare prodrug polymer carrier systems with the chemotherapeutic agent camptothecin (Cam) and the kinase inhibitor dasatinib (Dt). Abstract : Reversible addition–fragmentation chain transfer (RAFT) polymerization was employed to prepare prodrug polymer carrier systems with the chemotherapeutic agent camptothecin (Cam) and the kinase inhibitor dasatinib (Dt). Copolymers were prepared as dense polyethylene glycol brushes via direct copolymerization of the prodrug macromonomers with polyethylene glycol methacrylate (O950, FW ∼ 950 daltons). The brushes display controlled drug release profiles with little burst or late-phase release aberrations. Hydrolysis studies of the hydrophilic copolymers conducted in human serum showed 33 ± 1.7 and 22 ± 2.4% drug release over the course of 144 h for the ester linked Dt and Cam respectively. Polymer morphology was also shown to play a key role in drug release rates. Copolymers with the drug distributed in the copolymer segment showed faster release rates than diblock copolymers where the hydrophobic drug molecules were localized in discreet hydrophobic blocks. The latter materials were shown to self-assemble into polymeric micelles with the drug block separated from the aqueous phase. Live animal imaging in PC-3 (human prostate cancer cell line) tumor xenographs showed that the fluorescently labeled copolymer brushes were trafficked to the tumor 24 hours post injection. Ex vivo analysis of the harvested tissues showed that polymer accumulated in the tumor with kidney excretion. In vitro cytotoxicity measurements conducted in K562-S and K562-R cells demonstrated ability of the macromolecular conjugates to release active drugs. The direct copolymerization of different drug classes into controlled copolymers via RAFT, together with their favorable release profiles, suggest these carriers merit further study as therapeutic systems.